2022
DOI: 10.1371/journal.pone.0271391
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged mechanical ventilation in patients with severe COVID-19 is associated with serial modified-lung ultrasound scores: A single-centre cohort study

Abstract: Lung ultrasound (LUS), a rapid, bedside, goal-oriented diagnostic test, can be quantitatively assessed, and the scores can be used to evaluate disease progression. However, little data exists on predicting prolonged mechanical ventilation (PMV) and successful extubation using serial LUS scores. We examined the relationship of PMV with successful extubation in patients with severe coronavirus disease (COVID-19) by using two types of serial LUS scores. One LUS score evaluated both the pleura and lung fields, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The intercostal approach is recommended in the Soldati score [36] and the modified LUS score [47], where not only whether the pleura is involved but also its appearance (i.e., indented or broken in the Soldati score, irregular or blurred in the modified LUS score) is considered. In particular, the modified LUS score evaluates the parenchyma and the pleura separately, which may provide an advantage in prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercostal approach is recommended in the Soldati score [36] and the modified LUS score [47], where not only whether the pleura is involved but also its appearance (i.e., indented or broken in the Soldati score, irregular or blurred in the modified LUS score) is considered. In particular, the modified LUS score evaluates the parenchyma and the pleura separately, which may provide an advantage in prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Dargent et al proposed a score in which a rating of 27 is related to extubation failure and prompt need for NIV support [46]. Conversely, a reduction of the modified LUS score is associated with successful extubation [47].…”
Section: Lung Ultrasound Scores For Predicting Severity Treatment Res...mentioning
confidence: 99%
“…The chance of developing ventilator-induced pulmonary strain injuries with the length of time a patient is on respiratory support, and lung damage increases with time. [14].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Noncardiogenic pulmonary edema is a critical characteristic of both the pathogenesis and prognosis of ARDS [8], but the current methods for quantifying the severity of pulmonary edema are invasive (e.g., right cardiac catheterization) or time consuming (e.g., computed tomographic imaging). The Radiographic Assessment of Lung Edema (RALE) score is a proposed method for evaluating the density and extent of opacities on chest radiographs in patients diagnosed with ARDS; it can be utilized to assess both the degree of pulmonary edema and the severity of ARDS [9][10][11][12][13][14]. Jabaudon et al reported that changes in the RALE score during the first 3 days after admission to the intensive care unit (ICU) are linked to the survival rate of patients who have ARDS [10].…”
Section: Introductionmentioning
confidence: 99%